Environmental criteria when assessing the effectiveness of projects and development programs: Ensuring sustainability and economic security - Abdulkadyrov Arsen; Semenova Liliya; Suleymanova Tamila (BIO Web of Conferences)
Currently, the study of environmental criteria when assessing the effectiveness of development projects and programs has deep relevance in the modern environment of sustainable development discourse. At its core, the theme is a cross-cutting issue where environmental imperatives converge with socio-economic needs, embodying the imperative to combine environmental protection with economic prosperity. Understanding the environmental criteria embedded in project evaluation is critical because of the inherent interdependencies between human activities and ecological systems. Moreover, the study of environmental criteria contributes to a more detailed understanding of the dynamics of sustainability, outlining pathways towards sustainable and regenerative development trajectories. Sustainable development depends on reconciling environmental integrity with socio- economic progress, which requires the adoption of holistic approaches that go beyond simple mitigation of environmental impacts. By clarifying environmental thresholds and tipping points associated with development projects and programs, integrating environmental criteria facilitates the identification of sustainability bottlenecks and the formulation of adaptive management strategies.